Factores psicológicos relacionados a La procrastinación y la ansiedad en estudiantes universitarios de la ciudad de Cartago y Pereira. (2021)
According to the definition of Steel (2007), procrastination is a pattern of behaviors that is characterized by delaying or postponing the performance of a task assigned by others or by oneself. Anxiety has also been evidenced in college students who show procrastination, especially in the last semesters.